Adverse prognosis and distinct progression patterns after concurrent chemoradiotherapy for glioblastoma with synchronous subventricular zone and corpus callosum invasion. Issue 1 (January 2016) - Liang, Tony Hsiang-Kuang; Kuo, Sung-Hsin; Wang, Chun-Wei; Chen, Wan-Yu; Hsu, Che-Yu; Lai, Shih-Fan; Tseng, Ham-Min; You, San-Lin; Chen, Chung-Ming; Tseng, Wen-Yih Isaac
Abstract: Background and purpose: The subventricular zone (SVZ) and the corpus callosum (CC) invasion status are separately associated with adverse prognosis for glioblastoma. We investigated the prognosis and progression patterns of glioblastoma with and without synchronous SVZ and CC (sSVZCC) invasion. Material and methods: Glioblastoma patients completing concurrent chemoradiotherapy with temozolomide were retrospectively categorized by the preoperative sSVZCC invasion status. The associations between sSVZCC invasion and the survival and progression patterns were analyzed. Results: In total, 108 patients, including 36 with sSVZCC invasion, were followed for a median period of 60.2 (range 34.2–86.3) months. The median overall survival (OS) of patients with and without sSVZCC were 18.6 and 26.4 months, respectively ( p = 0.005). Using multivariate analyses with the factors of age, performance, surgery extent, and tumor size, sSVZCC invasion remained significant for a poor OS (hazard ratio, 1.96; 95% confidence interval, 1.19–3.21). The rates of progression at tumor bed, preoperative edematous areas, bilateral hemispheres, and ventricles for tumors with and without sSVZCC invasion were 75% and 63.9% ( p = 0.282), 41.7% and 9.7% ( p < 0.001), 47.2% and 13.9% ( p < 0.001), and 38.9% and 13.9% ( p = 0.006), respectively. Conclusions: The sSVZCC invasion status determined the distinct prognosis and progression areas of glioblastoma, which suggests individualized radiotherapy and drug administration strategies.